1998
DOI: 10.1029/1998gl900062
|View full text |Cite
|
Sign up to set email alerts
|

Nitric acid scavenging by mineral and biomass burning aerosols

Abstract: Abstract. The abundance of gas phase nitric acid in the upper troposphere is overestimated by global chemistry-transport models, especially during the spring and summer seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 23 publications
0
87
1
Order By: Relevance
“…Laboratory experiments have shown that HNO 3 uptake on mineral dust is promoted by its alkalinity Underwood et al, 2001;Michel et al, 2002;Hanisch and Crowley, 2003). Field measurements also support HNO 3 uptake (Tabazadeh et al, 1998;Thakur et al, 1999). Rapid sedimentation of nitrate on mineral dust could reduce recycling of NO x from HNO 3 , and in turn O 3 , with lower tropospheric O 3 decreases of 8-30% over and downwind of deserts (Bian et al, 2003;Bauer et al, 2004;Umann et al, 2005;Liao et al, 2005).…”
Section: Heterogeneous Chemistrymentioning
confidence: 91%
“…Laboratory experiments have shown that HNO 3 uptake on mineral dust is promoted by its alkalinity Underwood et al, 2001;Michel et al, 2002;Hanisch and Crowley, 2003). Field measurements also support HNO 3 uptake (Tabazadeh et al, 1998;Thakur et al, 1999). Rapid sedimentation of nitrate on mineral dust could reduce recycling of NO x from HNO 3 , and in turn O 3 , with lower tropospheric O 3 decreases of 8-30% over and downwind of deserts (Bian et al, 2003;Bauer et al, 2004;Umann et al, 2005;Liao et al, 2005).…”
Section: Heterogeneous Chemistrymentioning
confidence: 91%
“…It indicates that mineral dust particles are also transported into the upper troposphere by convection. 22,23 Therefore, it is significant to investigate the dependence of rate constants on the temperature for the heterogeneous reactions of trace gases on mineral dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…During dust storm events particle mass densities of up to 4650 µg m −3 are measured in the lower troposphere (Alfaro et al, 2003). Even at altitudes of 10 to 12 km, up to 500 ppt of mineral ions can be found in aerosol samples, indicating that these particles are also transported into the upper troposphere (Tabazadeh et al, 1998).…”
Section: Introductionmentioning
confidence: 99%